Insights Into the Synthetic Strategies, Biological Activity, and Structure- Activity Relationship of Pyridine and Analogs: A Review - Matthew, Aprajita; Kumar, Rajnish; Mazumder, Avijit; Salahuddin; Bhadauria, Harshita (Letters in Organic Chemistry, 2023)
Based on various research reports, pyridine possesses a wide range of pharmacological activities along with many other industrial applications. Because of its diverse applications, pyridine moiety is the center of attraction for researchers, and many patents have been granted focusing on it. Several synthetic protocols, such as cyclo-condensation, cyclization, cycloaddition, electrolysis, etc., were used by researchers to synthesize pyridine and analogs. Each synthetic protocol has merits and demerits and requires several types of reagents, catalysts, and reaction conditions. So, there is always a need for careful analysis of reported synthetic protocols whenever researchers like to initiate research on synthesizing pyridine and its analogs. The therapeutic activity of successfully marketed drugs might be possible because of the presence of pyridine in their structure. Any small alteration in the structure of the medicinal compounds may produce a major change in their pharmacological action. So, the correlation between the structure of its analogs with biological activity is also important. The proposed article also includes recently reported pharmacological activities and the structureactivity relationship of pyridine and its analogs. This article aims to help the researchers by highlighting recently reported methods for synthesizing pharmacologically useful pyridine analogs and their merits.
Keywords: marketed drugs